PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MURID KELAS III SD NEGERI LATSARI TUBAN - Nadhin Nazhela Putri; Sri Cacik; Novita Dewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve the mathematics learning outcomes of Grade III-B students at UPT SD Negeri Latsari Tuban through the implementation of the Numbered Heads Together (NHT) cooperative learning model. This study is a Classroom Action Research (CAR) project conducted over two cycles, with each cycle comprising four stages: planning, implementation, observation, and reflection. The research subjects were the 27 students of Grade III-B at UPT SD Negeri Latsari Tuban. Data collection techniques included learning outcome tests, student activity observation sheets, and teacher performance observation sheets. The results indicate a significant improvement in mathematics learning outcomes. In the initial condition (pre-cycle), the student mastery rate was only 37%. Following the implementation of the Numbered Heads Together (NHT) cooperative learning model, the mastery rate rose to 67% in Cycle I and reached the success indicator of 93% in Cycle II. Thus, the implementation of the Numbered Heads Together (NHT) cooperative learning model is proven to effectively improve the mathematics learning outcomes of Grade III-B students at UPT SD Negeri Latsari Tuban